2004
DOI: 10.1292/jvms.66.1283
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microflora in 45 Crows in Ueno Zoo and the in vitro Susceptibilities of 29 Escherichia coli Isolates to 14 Antimicrobial Agents

Abstract: ABSTRACT. Microorganisms from 45 jungle crows (Corvus macrorhynchos) captured from July to December 2002 at Ueno Zoo, Tokyo were identified as Escherichia coli, Proteus mirabilis, Klebsiella pneumoniae, Klebsiella oxytoca, Enterobacter aerogenes, Enterobacter cloacae, Enterobacter agglomerans, Pseudomonas maltophila, Staphylococcus spp., Micrococcus spp., and Streptococcus spp. E. coli showed the highest rate of isolation (21.6%). In an in vitro susceptibility test for 29 isolates of E. coli to 14 antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Microorganisms' populations that collectively comprise microbiota in crow's digestive system are associated with rearing conditions and environment. The intestinal microbial communities do not only have an important role in host metabolism [2] but also relate with zoonosis and food poisoning to human, animals, and birds [3]. Crows are considered as potential sources for fecal contamination of water supplies and foods, and the pathogens are transmitted through the fecal-oral route when humans would consume those contaminated foods or water [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms' populations that collectively comprise microbiota in crow's digestive system are associated with rearing conditions and environment. The intestinal microbial communities do not only have an important role in host metabolism [2] but also relate with zoonosis and food poisoning to human, animals, and birds [3]. Crows are considered as potential sources for fecal contamination of water supplies and foods, and the pathogens are transmitted through the fecal-oral route when humans would consume those contaminated foods or water [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although microorganisms in the digestive tract of Jungle Crow have been studied by using conventional culture-based assays [3], sufficient coverage of nonabundant and unculturable microbial groups in the gut have not been obtained. Interestingly, in spite of its importance in the public health relevance, no information on crow gut microbiota is available.…”
Section: Introductionmentioning
confidence: 99%
“…It occupies different ecological niches, including household areas, city dumps, hospital dumps, and water sources like lakes, ponds, and rivers. The house crow has been shown to carry several human pathogenic bacteria in its intestines ( 25 , 26 ). A study on these samples demonstrated that 59% of the crows living on hospital waste were potential carriers of clinically relevant ESBL-producing E. coli and Klebsiella ( 19 ), and hospital waste has been reported as a potential source of antibiotic-resistant bacteria ( 19 , 27 ).…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…In the natural environment in which they live, several species of enterobacteria also occur, as they are ubiquitous, in soil or water. Thus, Enterobacteriaceae have been isolated mainly from omnivorous, piscivorous and healthy carnivore birds [46,48,49,50,51].…”
Section: Discussionmentioning
confidence: 99%